Bakti Sosial Skrining Gangguan Penglihatan Pada Masyarakat di Pesisir Pantai Kota Mataram, Nusa Tenggara Barat - Nasrul, Monalisa; Nintyastuti, Isna Kusuma; Suryani, Dewi; Affarah, Wahyu Sulistya (Universitas Mataram, 2024)
coastal population is a high risk population for eye disease correlated with ultraviolet exposures such as cataract and pterygium. cataract and ptergygium are among the leading causes of preventable blindness in Indonesia and West Nusa Tenggara. Eye health screening consists of interview based on questionnaires about demography and previous eye health examinations and eye examination. Eye examination includes visual acuity testing, anterior and posterior segment of the eyes, followed by intraocular examination. Eighty seven (87) subjects from South Ampenan District and Bangsal Beach, Tanjung Karang underwent the screening are mainly women (50.6%), age range 40-60 years old (52.9%), whose professions are fishermen (67.8%) and never had eye health check-up before (74.7%). The majority of the population have normal visual acuity (74.15%). Cataracts and pterygiums are diagnosed in 39.1% and 64.4% of the population. High cataract and pterygium incidence may reflect lack of awareness of eye health among the coastal population therefore further interventions from local health care provider are needed to establish the preventive and curative management in the near future.